Sleep Disordered Breathing in Children A Comprehensive Clinical Guide to Evaluation and Treatment - Kheirandish-Gozal, Leila; Gozal, David (Respiratory Medicine, 2012)
Sleep Disordered Breathing in Children: A Comprehensive Clinical Guide to Evaluation and Treatment is a comprehensive, timely and up-to-date review of pediatric  sleep disordered breathing (SDB) and offers a thorough focus on several key areas: namely, the normal development and maturation of the airway and breathing during sleep, the techniques that are in place for assessment of SDB in children, the clinical manifestations and characteristics of several pediatric populations at risk for SDB, the implications of SDB in various end-organ systems, and, finally, a critical review of the evidence on current therapeutic approaches.  This unique and complete text is of welcome interest to all practicing physicians and healthcare professionals who evaluate children with sleep problems -- namely pulmonologists, pediatricians, sleep physicians, pediatric neurologists, pediatric otolaryngologists, and family practitioners, as well as clinical researchers, pediatric nurse practitioners and respiratory therapists.  Written by a distinguished and international panel of authors who are renowned experts in their field and who offer an expanded view of the problems associated with SDB, Sleep Disordered Breathing in Children: A Comprehensive Clinical Guide to Evaluation and Treatment is an indispensible resource for all physicians who evaluate children for sleep-disordered breathing